2010
DOI: 10.1007/s10120-010-0548-1
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter phase II study of weekly paclitaxel plus S-1 combination chemotherapy in patients with advanced gastric cancer

Abstract: prognosis of advanced gastric cancer is still poor, chemotherapies were reported to improve the overall survival compared to the best supportive care in several studies [2][3][4]. Among the various active chemotherapeutic agents, cisplatin-based chemotherapy is the most commonly used worldwide. The V-325 study demonstrated that adding docetaxel (D) to a frequently used regimen of cisplatin and 5-fl uorouracil (CF) provided benefi ts with regard to overall survival, response rate, time to disease progression, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…Other observed treatment related toxicities such as fatigue, vomiting, diarrhea were well tolerated. In the study of Yuji Ueda (37), neutropenia occurred with Grade-3 intensity in 14 patients (25.9%), Grade-4 neutropenia was observed in 1 patient, and Grade-3 anemia was observed in 7 patients (13.0%). The Grade-3 nonhematological toxicities were diarrhea (9.3%), anorexia (7.4%) and nausea (7.4%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observed treatment related toxicities such as fatigue, vomiting, diarrhea were well tolerated. In the study of Yuji Ueda (37), neutropenia occurred with Grade-3 intensity in 14 patients (25.9%), Grade-4 neutropenia was observed in 1 patient, and Grade-3 anemia was observed in 7 patients (13.0%). The Grade-3 nonhematological toxicities were diarrhea (9.3%), anorexia (7.4%) and nausea (7.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Several Phase-I and Phase-II studies have reported the efficacy and toxicity of the weekly administration of paclitaxel and S-1 in AGC, suggesting that this regime is effective and safe for this kind of patients (38 -40). Yuji Ueda et al (37) reported that among 54 patients with AGC, an overall response rate of 46.3%, a median PFS of 6.0, and a median OS of 14.3 months are observed. In this multicenter Phase-II study on the weekly administration of paclitaxel plus S-1 combination chemotherapy, paclitaxel is administered at 50 mg/m 2 on days 1, 8 and 15 and S-1 at 80 mg/m 2 on days 1 -14 followed by 2 weeks off in a 28-day cycle.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that an alternative treatment schedule of S-1 (1-week administration followed by 1-week rest) may further reduce the toxicities and allow continuation of the therapy. Recent studies have shown enhanced antitumor activity of S-1 with paclitaxel in AGC [9][10][11][12]. Given the scarcity of study on biweekly S-1 and paclitaxel (SPA) as first-line chemotherapy in patients with metastatic or advanced gastric cancer, the actual efficacy and safety of this regimen is in need of more research.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising agents was paclitaxel (PTX) [8], which had shown beneficial results in single use or concurrent use with a fluoropyrimidine [9][10][11][12]. However, these studies were conducted as single-arm phase I-II trials.…”
Section: Introductionmentioning
confidence: 99%
“…We therefore planned a randomized phase-II trial to compare the following four treatment regimens: A, sequential 5-FU monotherapy followed by PTX monotherapy; B, sequential S-1 monotherapy followed by PTX monotherapy; C, concurrent 5-FU plus PTX [11]; and D, concurrent S-1 plus PTX [12]. The purpose of the study was twofold: (1) to compare S-1 with infusional 5-FU to determine which was the better partner of PTX, and (2) to compare a concurrent strategy with a sequential one, the latter strategy being the one that is widely used in Japanese general practice.…”
Section: Introductionmentioning
confidence: 99%